Cryo-EM structure of the SPFH-NfeD family protein complex QmcA-YbbJ - Tan, Kwan Ann (2024)
The SPFH (stomatin, prohibitin, flotillin, and HflK/C) protein family is universally present and encompasses the evolutionarily conserved SPFH domain. These proteins are predominantly localized in lipid raft and implicated in various biological processes. The NfeD (nodulation formation efficiency D) protein family is often encoded in tandem with SPFH proteins, suggesting a close functional relationship. Here, we elucidate the cryoelectron microscopy (cryo-EM) structure of the Escherichia coli QmcA-YbbJ complex belonging to the SPFH and NfeD families, respectively. Our findings reveal that the QmcA-YbbJ complex forms an intricate cage-like structure composed of 26 copies of QmcA-YbbJ heterodimers. The transmembrane helices of YbbJ act as adhesive elements bridging adjacent QmcA molecules, while the oligosaccharide-binding domain of YbbJ encapsulates the SPFH domain of QmcA. Our structural study significantly contributes to understanding the functional role of the NfeD protein family and sheds light on the interplay between SPFH and NfeD family proteins.